If Channel as an Emerging Therapeutic Target for Cardiovascular Diseases: A Review of Current Evidence and Controversies - Mengesha, Hayelom G.; Tafesse, Tadesse B.; Bule, Mohammed H. (Frontiers in Pharmacology, 2017)
In 2015, non-communicable diseases accounted for 39.5 million (70%) of the total 56.4 million deaths that occurred globally, of which 17.7 million (45%) were due to cardiovascular diseases. An elevated heart rate is considered to be one of the independent predictors and markers of future cardiovascular diseases. A variety of experimental and epidemiological studies have found that atherosclerosis, heart failure, coronary artery disease, stroke, and arrhythmia are linked to elevated heart rate. Although there are established drugs to reduce the heart rate, these drugs have undesirable side effects. Hence, the development of new drugs that selectively inhibit the heart rate is considered necessary. In the search for such drugs, almost four decades ago the If channel, also known as the “funny channel,” emerged as a novel site for the selective inhibition of heart rate. These If channels, with a mixed sodium and potassium inward current, have been identified in the sinoatrial node of the heart, which mediates the slow diastolic depolarization of the pacemaker of the spontaneous rhythmic cells. The hyperpolarization-activated cyclic nucleotide-gated (HCN) subfamily is primarily articulated in the heart and neurons that are encoded by a family of four genes (HCN1-4) and they identify the funny channel. Of these, HCN-4 is the principal protein in the sinoatrial node. Currently, funny channel inhibition is being targeted for the treatment and prevention of cardiovascular diseases such as atherosclerosis and stroke. A selective If channel inhibitor named ivabradine was discovered for clinical use in treating heart failure and coronary artery disease. However, inconsistencies regarding the clinical effects of ivabradine have been reported in the literature, suggesting the need for a rigorous analysis of the available evidence. The objective of this review is therefore to assess the current advances in targeting the If channel associated with ivabradine and related challenges.